2013
DOI: 10.1002/cite.201200182
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Natural Chabazite for Selective Catalytic Reduction of NOx with NH3

Abstract: The potential of the natural chabazite for the selective catalytic reduction (SCR) of NOx with NH 3 is evaluated in the present work. Activity tests were performed under technically relevant reaction and temperature conditions for the fresh and hydrothermally aged catalysts. The natural chabazite before and after alkaline removal as well as after iron and copper addition were compared. The structural as well as surface and bulk properties were elucidated by a variety of complementary characterization technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
22

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 53 publications
0
6
0
22
Order By: Relevance
“…32 The average oxidation state of the Fe sites at the probed position ( Figure 4) was evaluated by linear combination analysis using the reference spectra obtained during TPR of a Fe-ZSM-5 catalyst. 28 The results indicate a clear impact of NH 3 concentration on the overall oxidation state which is, however, stronger at the inlet of the catalyst bed. These variations do not correlate only with the catalytic activity 17 but can be furthermore related to the local concentration of NH 3 .…”
Section: Resultsmentioning
confidence: 90%
“…32 The average oxidation state of the Fe sites at the probed position ( Figure 4) was evaluated by linear combination analysis using the reference spectra obtained during TPR of a Fe-ZSM-5 catalyst. 28 The results indicate a clear impact of NH 3 concentration on the overall oxidation state which is, however, stronger at the inlet of the catalyst bed. These variations do not correlate only with the catalytic activity 17 but can be furthermore related to the local concentration of NH 3 .…”
Section: Resultsmentioning
confidence: 90%
“…As a result, the range of chemical shifts for most elements is small compared to the uncertainties in the determination of the values [ 64 ] and thus literature data can only be considered as trend indicators. For example, Gunter et al studied chabazite and found pronounced shifts for the Fe 2p 3/2 peak at 714.6 eV compared to 709.9–711.6 eV for Fe 2 O 3 and the Cu 2p 3/2 peak at 936.7 eV compared to 932.7–934.6 eV for CuO [ 55 , 65 ]. Ruiz-Serrano et al studied clinoptilolite and the Ca 2p 3/2 was shifted to 348.3 eV compared to 346.1–347.3 eV for CaO and the Fe 2p 3/2 peak was shifted to 713.3 eV [ 55 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…• S2: site where ammonia is stored at high temperature. Ammonia storage has been observed at high temperature over pure H/SSZ-13 [54,55] and therefore, in the same way as for S1, this site is likely a combination of both ammonia stored on Brönsted sites as well as copper sites and in the model this was lumped together in the S2 site. However, some of the ammonia adsorbed at high temperature is likely associated with copper active sites in order to produce SCR activity at high temperature.…”
Section: Reactionmentioning
confidence: 92%